Analisa Minat Mahasiswa Terhadap Penggunaan Layanan Internet Banking Bank BNI Syariah - Rosmida Mufti; Teguh Suripto (JESI (Jurnal Ekonomi Syariah Indonesia), 2020)
The development of technology and information at this time, affect changes in service to customers. One form of technology utilization in banking is the e-banking or internet banking application, which is a banking service product that uses the internet network. Meanwhile the volume of banking transactions using internet banking in Indonesia both in frequency and volume continues to increase. In 2014, the volume of internet banking reached Rp. 6,447 trillion, up 17.32% compared to the previous year. it turns out that internet banking users are also dominated by young age. We can see this from the results of a survey conducted by the Indonesian Internet Service Provider (APJII). From the survey, it is known that 49.52% of internet banking users are aged 19-34 years, then 29.55% are aged 35-54 years, and 4.24% are 54 years and older.This research method is quantitative descriptive, an approach that illustrates the problem based on data in the form of numbers, then analyzed further to conclusions. The analytical tool is the SPSS Statistics Program.The results of the study stated that the perception of benefits. Perceived ease and risk perception apparently partially has a significant influence on students' interest in using internet banking services at BNI Syariah Bank. Meanwhile simultaneously these three variables also have a significant influence on students' interest in using internet banking services at BNI Syariah bank. While the determination number shows that when the variable can explain the variable student interest in using internet banking services by 57.5%, while the rest is explained by other variables.